(-b +/- sqrt (b^2-4ac))/2a
= (-6 +/- sqrt (36-4*1*-7))/2
= (-6 +/- sqrt (36+28))/2
= (-6 +/- sqrt (64))/2
= (-6 +/- 8)/2
= 2/2 or -14/2
or 1 or -7
2007-01-27 10:37:34
·
answer #1
·
answered by TPmy 2
·
3⤊
0⤋
Book is correct; by inspection, the factors are (x+1)(x-7). The quantity under the radical is 64; the square root is 8, so you get (-6+8)/2 and (-6-8)/2, which are 1 and -7, respectively. Watch those signs!
2007-01-27 18:37:27
·
answer #2
·
answered by Anonymous
·
1⤊
1⤋
the book said the answers were -7 and 1...ok..
Factor completely the polynomial x^2+6x-7=0
(x+7)(x-1)=0
therefore x1= -7 and x2=1
Recheck all the adding and multiplying with the quadratic formula...
Cheers
2007-01-27 18:35:58
·
answer #3
·
answered by Anonymous
·
1⤊
1⤋
*You don't need to use the Quadtratic Equation but, if your teacher/book says to do so....
First: you have three values for three coefficients...
a = 1
b = 6
c = -7
Sec: replace the values with their corresponding variables...
x = [- 6+/- â(6^2 - 4(1)(-7))] / 2(1)
x = [- 6+/- â(6^2 - 4(1)(-7))] / 2
x = [- 6+/- â(36 - 4(1)(-7))] / 2
x = [- 6+/- â(36 - 4(-7))] / 2
x = [- 6+/- â(36 + 28)] / 2
x = [- 6+/- â(64)] / 2
x = [- 6+/- 8] / 2
Third: you have two solutions > one has addition, the other has subtraction...
1. x = [- 6 + 8] / 2
x = 2/2
x = 1
2. x = [- 6 - 8] / 2
x= - 14/2
x = -7
Solutions: 1 and -7
2007-01-27 19:08:37
·
answer #4
·
answered by ♪♥Annie♥♪ 6
·
0⤊
1⤋
the formula gives(-6 +-8)/2 = -7 and 1 because -b is -6
2007-01-27 19:48:19
·
answer #5
·
answered by santmann2002 7
·
0⤊
0⤋
x=-b屉b^2-4ac/2a
a=1,b=6,c=-7
x=(-6屉(6)^2-4(1*-7))/2(1)
x=(-6屉36+28))/2
x=(-6屉64))/2
x=(-6屉64)/2
x=-6±8/2
(-6-8)/2, (-6+8)/2
x=-7 and 1
You should negative and positive integers for your answer.
2007-01-27 18:46:40
·
answer #6
·
answered by Anonymous
·
1⤊
0⤋
x^2 + 6x - 7 = 0
x = 3.099363912
bound={-1EE99, 1EE99}
2007-01-27 18:44:05
·
answer #7
·
answered by Kevin H 7
·
0⤊
2⤋
are u making b negative
2007-01-27 18:39:46
·
answer #8
·
answered by The Watched 3
·
1⤊
1⤋